Reactive vaccination as a control strategy for pneumococcal meningitis outbreaks in the African meningitis belt: Analysis of outbreak data from Ghana. Issue 37 (3rd September 2019) - Cooper, Laura V.; Stuart, James M.; Okot, Charles; Asiedu-Bekoe, Franklin; Afreh, Osei Kuffour; Fernandez, Katya; Ronveaux, Olivier; Trotter, Caroline L.
Graphical abstract: Abstract: Streptococcus pneumoniae is increasingly recognised as an important cause of bacterial meningitis in the African meningitis belt. The World Health Organization sets guidelines for response to outbreaks of meningococcal meningitis, but there are no current guidelines for outbreaks where S. pneumoniae is implicated. We aimed to evaluate the impact of using a similar response to target outbreaks of vaccine-preventable pneumococcal meningitis in the meningitis belt. Here, we adapt a previous model of reactive vaccination for meningococcal outbreaks to estimate the potential impact of reactive vaccination in a recent pneumococcal meningitis outbreak in the Brong-Ahafo region of central Ghana using weekly line list data on all suspected cases over a period of five months. We determine the sensitivity and specificity of various epidemic thresholds and model the cases and deaths averted by reactive vaccination. An epidemic threshold of 10 suspected cases per 100, 000 population per week performed the best, predicting large outbreaks with 100% sensitivity and more than 85% specificity. In this outbreak, reactive vaccination would have prevented a lower number of cases per individual vaccinated (approximately 15, 300 doses per case averted) than previously estimated for meningococcal outbreaks. Since the burden of death and disability from pneumococcal meningitis is higher than that from meningococcal meningitis, there may still be merit in considering reactive vaccination for outbreaks of pneumococcal meningitis. More outbreak data are needed to refine our model estimates. Whatever policy is followed, we emphasize the importance of timely laboratory confirmation of suspected cases to enable appropriate decisions about outbreak response.